2012
DOI: 10.1136/heartjnl-2011-301599
|View full text |Cite
|
Sign up to set email alerts
|

Systemic to pulmonary collateral blood flow influences early outcomes following the total cavopulmonary connection

Abstract: CMR can provide an effective measurement of SPC flow prior to TCPC. Young age at BCPC, high preoperative oxygen saturation and smaller PAs are associated with increased SPC flow, which may promote increased postoperative pleural drainage and lengthen recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 12 publications
0
40
1
Order By: Relevance
“…In addition, we did not investigate the false positive cases (shunt detected by UD only) for the presence of extra cardiac shunts, which are common with some cardiac lesions [28,29]. Overall, the net effect may be to inflate the apparent false positive rate.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, we did not investigate the false positive cases (shunt detected by UD only) for the presence of extra cardiac shunts, which are common with some cardiac lesions [28,29]. Overall, the net effect may be to inflate the apparent false positive rate.…”
Section: Discussionmentioning
confidence: 92%
“…First, shunt flow may be significant, even in relatively small shunts, and also out of proportion to pressure gradients across chambers connected by the shunt [26,27]. Second, intra-and extra-cardiac shunts are not always apparent on echocardiography [2,3,28,29] and may need confirmation and quantification via alternative investigational modalities such as MRI or cardiac catheterization, which carry different risk profiles for the patient. Thus, UD may be a useful screening tool to evaluate patients who may need more detailed investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Highlighting the clinical significance of APC flow, three studies recently demonstrated that increased collateral flow before the Fontan operation was associated with longer duration of pleural drainage and prolonged recovery in the postoperative period [6][7][8]. However, the mentioned studies primarily focused on technical aspects of quantifying APC flow [2][3][4] or were assessed in patients after the Glenn-procedure [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have identified systemic to pulmonary collateral flow as associated with poorer post-Fontan outcomes (Figure 3). [15][16][17] In our model, as the collateral flow increased from 0 to 1.4 L/min (equivalent of 2.5 L/min/m 2 ), the ratio of pulmonary flow to systemic flow (Qp/Qs) increased from 1.0 to 3.2 ( Figure 3, top two panels). The ventricular output (Qcor þ Qs þ Qcoll) increased to 29% (from 2.8 to 3.6 L/min/m 2 ) because the ''effective circulatory resistance'' seen by the single ventricle is reduced; however, Qs, in this case the systemic flow exclusive of the collaterals, dropped from 1.5 L/min to 0.6 L/min.…”
Section: Acute Valvular Regurgitationmentioning
confidence: 91%